Optimal lot sizing model with reprocessing of defective output - Estanislao, Eppie V. (Animo Repository, 1993)
This study deals with minimizing the total system cost of asequential multi-stage production system which allows the reprocessing of defective components that could be obtained from each stage of the process. This model is applicable to the glass industry, metal industry, paper industry and plastic industry. The cost components of the model comprise of the set-up cost, carrying cost of in-process, finished goods and defective items, shortage cost and reprocessing cost. These costs are minimized at the optimal production lot size. The optimal reprocessing lot size is subsequently obtained from this. It is hoped that the model may not only serve to add to the body of knowledge on reprocessing but that it may prove practical and relevant to concerned industries.